The Effect of Problem-Based Learning Model on Mathematical Critical Thinking Skills of Junior High School Students: A Meta-Analysis Study - Yohannes Yohannes; Dadang Juandi; Maximus Tamur (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2021)
Numerous similar studies have been conducted to evaluate the effect of problem-based learning models (PBL) on students' mathematical critical thinking skills. However, the findings from these studies are inconsistent. Highlighting this gap, this study comprehensively evaluates the effectiveness of implementing the PBL model on junior high school students’ critical thinking skills. This meta-analysis study was conducted by analyzing a sample of 15 journal papers that met the feasibility. Empirical data collection uses several journal search engines, and the instruments used are coding categories. Data analysis to obtain effect size value was performed with Comprehensive Meta-Analysis (CMA) software, and the estimation method used a random-effect model. Overall, the results showed that the effect size of PBL model implementation on mathematical critical thinking skills of junior high school students is 0.970, which means the PBL model's implementation had a high effect on students' critical thinking skills. Besides, the effect size of implementing the PBL model on junior high school students' critical thinking skills did not differ based on differences in class, year of study, and sample size. However, there were significant differences in effect sizes between study groups based on treatment duration. Thus, PBL will achieve a higher level of effectiveness, taking into account the treatment duration.